(3fXGe GdZQjH aj GddZIs - (3YjSi Hf EHQGgje GdQHYj, CHh eMeO,J (B480 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNQL GdCTjGA ef GdYOe Edi GdhLhO HGH eG LGA ai GdZQjH ai Ndb GdEfSGf s
(3BNQgG (B:s
(3jfJgi HCKfGA HGH ai GdeLehY ELGHGJ Yf SDGd jYf s
(3GdfSNI HgG MhGTs
(3HdZ ebGHdI hbQGAI ddabjg GdCLd MSjf Hf eMeO Hf YHO Gddg GdfhGSjWis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B100s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1959s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs